2012
DOI: 10.4012/dmj.2011-131
|View full text |Cite
|
Sign up to set email alerts
|

The biomimetic apatite-cefalotin coatings on modified titanium

Abstract: Dental implant failure often occurs due to oral bacterial infection. The aim of this study was to demonstrate that antibiotic efficacy could be enhanced with modified titanium. First, the titanium was modified by anodization and heat-treatment. Then, a biomimetic coating process was completed in two steps. Surface characterization was performed with scanning electron microscopy, energy dispersive spectroscopy, and X-ray diffraction. Release of antibiotic was evaluated by UV/VIS spectrometry, and the antibacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…An interactive implant surface with pH-dependent or infection-dependent antibiotic release might avoid this shortcoming, but has not yet been introduced to dental implant materials research. Antibiotics are capable of reducing bacterial colonization with S. mutans 22,39) S. epidermidis 31) and S.aureus 38) , P. gingivalis, A. actinomycetemcomitans, P. intermedia, P. aeruginosa 40) and E. coli 21,23,36) on titanium surfaces. Chlorhexidine (CHX)-loaded titanium surfaces reduce colonization with streptococci and S. aureus in comparison to titanium control [24][25][26] .…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%
“…An interactive implant surface with pH-dependent or infection-dependent antibiotic release might avoid this shortcoming, but has not yet been introduced to dental implant materials research. Antibiotics are capable of reducing bacterial colonization with S. mutans 22,39) S. epidermidis 31) and S.aureus 38) , P. gingivalis, A. actinomycetemcomitans, P. intermedia, P. aeruginosa 40) and E. coli 21,23,36) on titanium surfaces. Chlorhexidine (CHX)-loaded titanium surfaces reduce colonization with streptococci and S. aureus in comparison to titanium control [24][25][26] .…”
Section: Drug-loaded Surfacesmentioning
confidence: 99%
“…A localized treatment with antibiotics provides a sustained release. Typical coating matrices for controlled release systems are polyesters such as poly‐ε‐caprolactone, biodegradable polymers such as alginate, poly(lactic acid), poly(glycolic acid), and carbonated hydroxyapatite . Biodegradable polymers are extensively employed in periodontal drug delivery devices due to their abundance, lack of toxicity, and high biocompatibility .…”
Section: Peri‐implantitis Prevention: Antimicrobial Coatingsmentioning
confidence: 99%
“…Typical coating matrices for controlled release systems are polyesters such as poly-ε-caprolactone, 99 biodegradable polymers such as alginate, poly(lactic acid), poly(glycolic acid), 100 and carbonated hydroxyapatite. 101,102 Biodegradable polymers are extensively employed in periodontal drug delivery devices due to their abundance, lack of toxicity, and high biocompatibility. 103 Antibiotic-carbonated hydroxyapatite coatings have been applied to titanium-based devices to improve fixation and to control infection.…”
Section: Peri-implantitis Prevention: Antimicrobial Coatingsmentioning
confidence: 99%
“…When titanium is immersed in a simulated body fluid (SBF) at the physiological pH value and temperature, a CaP layer can be formed on its surface 15,16) . This CaP coating has been proved to be able to facilitate new bone formation and integration with surrounding bone tissue due to its chemical composition, biocompatibility and osteoconductivity [17][18][19][20] . In addition, it is an ideal carrier for organic molecules that contain carboxylic groups such as BMP-2, vascular endothelial growth factor (VEGF) and antibiotics 17,19,21,22) .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is an ideal carrier for organic molecules that contain carboxylic groups such as BMP-2, vascular endothelial growth factor (VEGF) and antibiotics 17,19,21,22) . When these organic molecules are dissolved in the saturated SBF solution containing calcium and phosphate, they can co-precipitate with the minerals simultaneously, since carboxylic groups have strong binding affinity to calcium ions 18) . Previous study has demonstrated that recombinant human bone morphogenetic proteins 2 (rhBMP-2) incorporated in CaP coating is potent in stimulating the alkaline phosphatase (ALP) activity of the adhering cells 23) .…”
Section: Introductionmentioning
confidence: 99%